Timed Get Up and Go Implementation to Improve Falls Assessment - (:unkn) unknown (My University, 2020)
Falls are a large problem in the geriatric population, causing injury to patients and financial strain on the healthcare system. Using Meleis Transition theory and Lewin’s Change theory as a framework, the author implemented a standardized process to evaluate fall risk in a small, suburban primary care practice. The site had a large patient base who were > 65 years of age, making them high risk for falls with no falls assessment in place, which is why it was chosen as the project site. The medical assistants were educated on the STEADI initiative and the project protocol during a live session that was accompanied by a PowerPoint presentation. The medical assistants used the STEADI Algorithm to determine if the patient needs further assessment. If the algorithm determined further assessment was needed, then the patient completed a Timed Get Up and Go, which was documented in the EHR. The adherence rate to TUG assessment was 33% post implementation, which was lower than the target adherence rate of 50%. However, awareness of the issue was raised with this project. The author found that implementing change in a small practice is difficult, but can positively affect patients and the healthcare system, meeting the goals of the Triple Aim and Healthy People 2020.
Keywords: STEADI; Falls; TUG; Geriatric